The prayer box [large type] - Wingate, Lisa (Thorndike Press, 2013)
When Hatteras Island old-timer Iola Anne Poole passes away at ninety-one, the struggling young mother in her rental cottage finds herself charged with cleaning out Iola's rambling Victorian house. Running from a messy, dangerous past, Tandi Jo Reese never expects to find more than a temporary hiding place within Iola's walls. But all that changes when she discovers eighty-one carefully decorated prayer boxes. Hidden in the boxes is the story of a life of an unassuming but complex woman passing through the seasons of an extraordinary, unsung life filled with journeys of faith, observations on love, and one final lesson that could change everything for Tandi.